2021
DOI: 10.1093/tas/txab015
|View full text |Cite
|
Sign up to set email alerts
|

The effects of high-oleic peanuts as an alternate feed ingredient on performance, ileal digestibility, apparent metabolizable energy, and histology of the small intestine in laying hens

Abstract: We aimed to determine the effects of feeding a high-oleic peanut (HOPN) diet to egg-producing laying hens on egg quality, digestibility, and feed conversion. Three isonitrogenous and isocaloric dietary treatments were formulated with 1) Control diet (CON) - a corn-soybean meal conventional diet with 7.8 % added poultry fat 2) HOPN diet - dietary inclusion of ~20% coarse-ground whole HOPN and 3) Oleic Acid (CON-OA) diet -a control diet supplemented with 2.6 % oleic fatty acid oil. Ninety-nine 57-wk-old brown Le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 32 publications
1
10
0
Order By: Relevance
“…However, the high-oleic peanut (HOPN) treatment group had a significantly higher AMEn than the other two treatments 2 . In parallel, Redhead et al 3 reported significantly higher AMEn levels for their high oleic peanut dietary treatment group as compared to the conventional control in a layer feeding trial. The ileal protein digestion was also greater in hens fed the high oleic peanut-containing diets compared to the conventional controls.…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…However, the high-oleic peanut (HOPN) treatment group had a significantly higher AMEn than the other two treatments 2 . In parallel, Redhead et al 3 reported significantly higher AMEn levels for their high oleic peanut dietary treatment group as compared to the conventional control in a layer feeding trial. The ileal protein digestion was also greater in hens fed the high oleic peanut-containing diets compared to the conventional controls.…”
Section: Introductionmentioning
confidence: 94%
“…Hence it is important to understand that these feed ingredients can replace corn fully or partially, without having negative effects on production performance 1 . Some research has examined how feeding high-oleic peanuts affects production performance of both broilers and laying hens 2,3 , while others have evaluated how feeding sweet potato roots, vines and peels would affect poultry performance 3 . Most feeding trials have only examined the performance and production aspects of these alternative feed ingredients but it is also important to understand the nutrient digestibility of these ingredients when fed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that feeding peanut meal prepared from normal-oleic peanuts as a good alternative that does not hinder performance [1][2][3] . Some research has shown that feeding a diet containing high-oleic peanuts could also be a viable alternative in both laying hens as well as broilers [4][5][6][7] . However, there is very little research on how digestible a diet including peanuts is for poultry and specifically laying hens.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, whole unblanched (skin intact) peanuts may serve as a nutrient-rich value-added alternative feed ingredient for animal food production while reducing the production of agricultural waste by-products from the peanut industry. Thus, numerous studies have been conducted to explore the effective utilization of peanuts and/or peanut by-products within the animal feed as value-added feed components [3][4][5][6][7][8][9][10] and to enhance agricultural sustainability.…”
Section: Introductionmentioning
confidence: 99%